Long‐term follow‐up of children with high‐risk neuroblastoma: The ENSG5 trial experience12. Issue 7 (31st December 2012) - Moreno, Lucas; Vaidya, Sucheta J.; Pinkerton, C. Ross; Lewis, Ian J.; Imeson, John; Machin, David; Pearson, Andrew D. J.; ,
Abstract Background Therapy for high‐risk neuroblastoma is intensive and multimodal, and significant long‐term adverse effects have been described. The aim of this study was to identify the nature and severity of late complications of metastatic neuroblastoma survivors included in the ENSG5 clinical trial. Procedure The trial protocol included induction chemotherapy (randomized "Standard" OPEC/OJEC vs. "Rapid" COJEC), surgery of primary tumor and high‐dose melphalan with stem cell rescue. Two hundred and sixty‐two children were randomized, 69 survived >5 years, and 57 were analyzed. Data were obtained from the ENSG5 trial database and verified with questionnaires sent to participating centers. Results Median follow‐up was 12.9 (6.9–16.5) years. No differences were found in late toxicities between treatment arms. Twenty‐eight children (49.1%) developed hearing loss. Nine patients (15.8%) developed glomerular filtration rate <80 ml/min/1.73 m2, but no cases of chronic renal failure were documented. Endocrine complications (28.1% of children) included mainly hypogonadism and delayed growth. Four children developed second malignancies, three of them 5 years after diagnosis: one osteosarcoma, one carcinoma of the parotid gland and one ependymoma. There were no hematological malignancies or deaths in remission. Conclusions This study analyzed a wide cohort of high‐risk neuroblastoma survivors from a multi‐institutional randomized trial and established the profile of long‐term toxicity within the setting of an international clinical trial. Pediatr Blood Cancer 2013; 60: 1135–1140. © 2012 Wiley Periodicals, Inc.